Depth-Dependent Environmental Drivers of Microbial Plankton Community Structure in the Northern Gulf of Mexico - Easson, Cole G.; Lopez, Jose V. (Frontiers in Microbiology, 2019)
The Gulf of Mexico (GoM) is a dynamic marine ecosystem influenced by multiple natural and anthropogenic processes and inputs, such as the intrusion of warm oligotrophic water via the Loop Current, freshwater and nutrient input by the Mississippi River, and hydrocarbon inputs via natural seeps and industrial spills. Microbial plankton communities are important to pelagic food webs including in the GoM but understanding the drivers of the natural dynamics of these passively distributed microorganisms can be challenging in such a large and heterogeneous system. As part of the DEEPEND consortium, we applied high throughput 16S rRNA sequencing to investigate the spatial and temporal dynamics of pelagic microbial plankton related to several environmental conditions during two offshore cruises in 2015. Our results show dramatic community shifts across depths, especially between photic and aphotic zones. Though we only have two time points within a single year, observed temporal shifts in microbial plankton communities were restricted to the seasonally influenced epipelagic zone (0–200 m), and appear mainly driven by changes in temperature. Environmental selection in microbial plankton communities was depth-specific, with variables such as turbidity, salinity, and abundance of photosynthetic taxa strongly correlating with community structure in the epipelagic zone, while variables such as oxygen and specific nutrient concentrations were correlated with community structure at deeper depths.